2020
DOI: 10.21037/tlcr-20-192
|View full text |Cite
|
Sign up to set email alerts
|

Compare the efficacy and safety of programmed cell death-1 (PD-1) and programmed cell death ligand-1 (PD-L1) inhibitors for advanced non-small cell lung cancer: a Bayesian analysis

Abstract: Background: Inhibitors of programmed cell death-1 (PD-1) and its ligand (PD-L1) have represented a novel approach for the management of advanced non-small cell lung cancer (NSCLC). In this study, we aimed to estimate five anti-PD-1/L1 agents (nivolumab, pembrolizumab, atezolizumab, durvalumab, and avelumab) using network meta-analyses (NMAs) and the Bayesian method to provide suggestions for advanced NSCLC treatments.Methods: We searched PubMed, Web of Science, Embase, and the Wiley Online Library for eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
1
20
1
Order By: Relevance
“…Some authors found no benefit with nivolumab in terms of OS, PFS, or overall response rate, but for a lower percentage of grades 3 or 4 AEs [ 56 ], nivolumab has been associated with significantly longer overall survival, and has a good safety profile in both squamous [ 5 ] and non-squamous NSCLC [ 7 ]. Compared with other PD-1 inhibitors (pembrolizumab and atezolizumab), nivolumab has been estimated as the best option in terms of anti-tumor efficacy, while atezolizumab is better at reducing adverse events, and pembrolizumab monotherapy was shown to be the best especially for patients with PD-L1 ≥ 50% [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found no benefit with nivolumab in terms of OS, PFS, or overall response rate, but for a lower percentage of grades 3 or 4 AEs [ 56 ], nivolumab has been associated with significantly longer overall survival, and has a good safety profile in both squamous [ 5 ] and non-squamous NSCLC [ 7 ]. Compared with other PD-1 inhibitors (pembrolizumab and atezolizumab), nivolumab has been estimated as the best option in terms of anti-tumor efficacy, while atezolizumab is better at reducing adverse events, and pembrolizumab monotherapy was shown to be the best especially for patients with PD-L1 ≥ 50% [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the understanding of the biology of this cancer has rapidly increased and the use of targeted therapy with tyrosine kinase inhibitors (TKIs) improve the management of patients with oncogenic driven cancers and their survival rates. Major progress was made with the emergence of the immunotherapy with reduced overall toxicity and almost complete absence of non-specific side effects compared to chemotherapy and other classic cancer therapies, but with specific toxicity profiles depending on the mechanisms of action [ 5 , 6 , 7 ]. In this regard, immunotherapy targeting programmed cell death-1 (PD-1) and programmed cell death-ligand 1 (PD-L1) has markedly improved the overall survival (OS) of patients, not only in those with metastatic NSCLC, but also in patients with locally advanced disease and extensive-stage small-cell lung cancer [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the use of targeted therapy with tyrosine kinase inhibitors improved patient management and their survival rates [ 6 ]. In turn, the emergence of immunotherapy, with reduced overall toxicity and non-specific side effects compared to chemotherapy and other classic cancer therapies, has been a great leap forward [ 7 , 8 ]. As a matter of fact, current evidence indicates that immunotherapy’s efficacy (overall survival, objective response rate and progression free survival) is superior to traditional standard chemotherapy in first line treatment for some types of cancer [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment of advanced solid-organ malignancies with immunotherapy compared with traditional chemotherapy is associated with a lower risk of adverse events (AEs) [ 11 ]. However, immunotherapy presents specific toxicity profiles depending on its mechanisms of action [ 7 , 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation